The effectiveness of therapeutic horseback riding activity for child development / Nurul Akmaniza Mohd Nasir and Nur Aqilah Muhammad Som - Mohd Nasir, Nurul Akmaniza; Muhammad Som, Nur Aqilah (UiTM Cawangan Negeri Sembilan, 2022)
What Is Therapeutic Horseback Riding? Therapeutic horseback riding activity is a horseback riding session that emphasizes the development of physical, psychological and social functions among riders (Patterson, 2015). Horseback riding activity may be one of the recreational activities among Malaysian in public parks or open spaces such as animal gardens. Although therapeutic horseback riding was developed with an instructor and side walkers on either side of the horse, it may not be well-liked in Malaysian culture. It is also a cutting- edge therapeutic approach that has been validated as a form of therapy programme for kids with certain developmental difficulties. During the therapy program, an instructor will have the responsibility to teach the riders to properly ride a horse and eventually improve the rider’s cognitive skills, emotional level and physical well-being. Additionally, Frank Anderson (2013), a journalist from a Pegasus Park, USA, equestrian centre stated that while horseback riding may be used as a therapeutic technique for children with disabilities, it also has the same positive effects on healthy youngsters.